(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
The full knowledge of the normal fetal fluids composition could be useful in the dog for the better management of newborns. The aim of the present study was to define the biochemical composition of amniotic fluid of puppies born by elective Caesarean section (CS) at term of pregnancy. The study enrolled 24 purebred bitches, classified into small size (<10 kg) and large size breeds (>20kg). All the bitches were healthy and clinically monitored from mating until parturition. For all the bitches an elective CS at term of pregnancy was performed [1]. For each puppy, the amniotic fluid was collected, immediately centrifuged and frozen at – 20° C until analysis for ALB, AMY, TB, CHOL, CK, ALP, GGT, AST, ALT, LDH, Mg, Ca, K, Na, Trig, BUN, Glc, TP, CREA, LIP, Cl, and GLOB. Data were analyzed by ANCOVA to verify the possible effects of parity, breed body size and newborn gender on amniotic biochemical composition. A total of 69 amniotic fluid samples were collected. The amniotic mean±SD and min-max values for each parameter were defined. LDH (p<0.01) and CK activity (p<0.05), as well as Glc concentrations (p<0.0001) were negatively influenced by the parity. AMY activity was significantly (p<0.05) higher in large sized (44.2±20.87 U/L) respect to small sized dogs (30.3±19.89 U/L), while lower (p<0.05) CHOL amniotic concentrations were found in small sized (3.0±2.71 mg/dl) as compared to large sized (3.9±2.93 mg/dl) dogs. Gender of the newborn did not influence the amniotic biochemical composition. The preliminary results of this study showed some similarities as well as some differences concerning the biochemical composition of the amniotic fluid in dogs at term of pregnancy if compared to data reported for the cat [2]. Furthermore, the results suggested that, in dogs, some amniotic parameters could be influenced by breed body size and by parity.